Reck-Notch1 Signaling Mediates miR-221/222 Regulation of Lung Cancer Stem Cells in NSCLC - Guo, Yuefan; Wang, Guangxue; Wang, Zhongrui; Ding, Xin; Qian, Lu; Li, Ya; Ren, Zhen; Liu, Pengfei; Ma, Wenjing; Li, Danni; Li, Yuan; Zhao, Qian; et al. (Frontiers in Cell and Developmental Biology, 2021)
Cancer stem cells (CSCs) contribute to the cancer initiation, metastasis and drug resistance in non-small cell lung cancer (NSCLC). Herein, we identified a miR-221/222 cluster as a novel regulator of CSCs in NSCLC. Targeted overexpression or knockdown of miR-221/222 in NSCLC cells revealed the essential roles of miR-221/222 in regulation of lung cancer cell proliferation, mammosphere formation, subpopulation of CD133+ CSCs and the expression of stemness genes including OCT4, NANOG and h-TERT. The in vivo animal study showed that overexpression of miR-221/222 significantly enhanced the capacity of lung cancer cells to develop tumor and grow faster, indicating the importance of miR-221/222 in tumorigenesis and tumor growth. Mechanistically, Reck was found to be a key direct target gene of miR-221/222 in NSCLC. Overexpression of miR-221/222 significantly suppressed Reck expression, activated Notch1 signaling and increased the level of NICD. As an activated form of Notch1, NICD leads to enhanced stemness in NSCLC cells. In addition, knockdown of Reck by siRNA not only mimicked miR-221/222 effects, but also demonstrated involvement of Reck in the miR-221/222-induced activation of Notch1 signaling, verifying the essential roles of the miR-221/222-Reck-Notch1 axis in regulating stemness of NSCLC cells. These findings uncover a novel mechanism by which lung CSCs are significantly manipulated by miR-221/222, and provide a potential therapeutic target for the treatment of NSCLC.